Prevalence and predictors of self-rated health status among a nationally representative population-based sample of older adults in India in 2017-2018 - Supa Pengpid (2022)
This chapter aimed to determine the prevalence and predictors of self-rated health (SRH) in older adults in India. The cross-sectional sample consisted of 52,393 individuals (≥50 years) from the Longitudinal Ageing Study in India (LASI) Wave 1 in 2017-2018. SRH was assessed with one single item. Results indicate that the prevalence of fair or poor SRH was 43.3%. In adjusted binary and ordered logistic regression analyses, older age, medium level of education, Muslim, Sikh, underweight, arthritis, diabetes, asthma, angina, stroke and functional disability were associated with poorer SRH (poor or fair SRH and poorer SRH as a scale), while subjective socioeconomic status, and vigorous physical activity were negatively associated with poorer SRH (poor or fair SRH and poorer SRH as a scale). In addition, current tobacco use and hypertension were associated with poor or fair SRH, and heart disease was associated with poorer SRH (as scale). Almost one in two older adults in India had fair or poor SRH. Several risk factors were identified, which can be targeted in public health interventions.